RANCANG BANGUN IDENTIFIKASI IDENTITAS MENGGUNAKAN RFID BERBASIS ESP32 UNTUK SMART PARKING SYSTEM DI FAKULTAS TEKNIK UB - Imet Mitsuin Banjar Nahor; Eka Maulana; Akhmad Zainuri (Jurnal Mahasiswa TEUB, 2023)
The parking area at Universitas Brawijaya which functions as a vehicle storage place for students and the academic community is often used by people outside UB because the condition of the portal in and out of the parking area is always open. In full parking conditions, students must enter the parking area to check the parking quota because there is no information on parking availability and this causes mobilization in the parking area to be disrupted. To overcome this problem, it is necessary to create an RFID-based smart parking monitoring system that functions to scan RFID tags as a condition for opening portals and parkingarea access. In this smart parking system, testing is carried out using a design (prototype) that is in accordance with actual parking conditions. The parking system is equipped with an RFID reader, servo actuator that functions as a portal, seven segment display as parking availability information and ultrasonic sensors as distance detection to close the portal. From the results of the study, the tools made are able to work according to the expected functions. Information on parking availability on the display is 100% in accordance with actual conditions, RFID reading positions are most effective at an angle of 90Âº with a maximum reading distance of 4 cm. RFID readers are capable of reading RFID tags a maximum of 2cm in the state where the RFID tag is in a wallet. The ultrasonic sensor in this study works with a maximum distance of 25 cm. Keywords: Smart parking, Prototype,RFID, ultrasonic sensor, RFID Reader,RFID tag,actuator,